Epigenetic regulation of transcription factor STAT3 activity in cancer cells - Seghal, Pravin D. (Contemporary Oncology/Współczesna Onkologia, 2006)
The transcription factor STAT3 is increasingly viewed as an oncogene. Activated STAT3 is pro-proliferative, anti-apoptotic and oncogenic. There is growing evidence for the epigenetic regulation of STAT3 activity in cancer cells. We and others have previously reported that STAT3 activity in breast cancer and in lung endothelial and epithelial cells was inversely regulated by the tumor suppressor protein caveolin-1 (cav-1). In order to understand the mechanisms involved, we reexamined how STAT3 signaling, which is initiated in plasma membrane raft microdomains, traverses the cytoplasm to the nucleus. Using cell-fractionation methods, we observed that by 15-30 min. after IL-6 treatment, up to two thirds of cytoplasmic Tyr-phosphorylated STAT3 can be associated with the purified early endosome (EE) fraction (Rab-5-, EEA1-, TfR- and clathrin-positive fraction). Electron microscopy, immunofluorescence and detergent-dissection approaches confirmed the association of STAT3 and PY-STAT3 with early endosomes. STAT3-transcriptional activation was inhibited by expression constructs for dominant negative dynamin K44A, epsin 2a, ampiphysin A1 and clathrin light chain, but enhanced by that for the active dynamin species MxA. Moreover, overexpression of the tumour suppressor cav-1 negatively regulated STAT3 signaling. Taken together, the data demonstrate strong epigenetic regulation of STAT3 signaling in cancer cells by virtue of dynamic membrane-associated trafficking along the caveolar (negative regulation) and endocytic (positive regulation) pathways.